Risk Factors of Subjective Cognitive Decline among Older People with Low Socioeconomic Status - Muhamad Nazri, Ameer Izzuddin; Vanoh, Divya; Leng, Soo Kah; Badrasawi, Manal (Jurnal Gizi dan Pangan, 2023)
The aim of the study is to investigate the predictors associated with Subjective Cognitive Decline (SCD)especially among older people with low socioeconomic status. This was a cross- sectional study involving older people with low socioeconomic status in Kelantan, which is one of the poorest states in Malaysia. Data of anthropometry, body composition, cognitive function, sarcopenia, depressive symptoms, medical history, blood pressure and polypharmacy were obtained via face-to-face interview. SCD was determined by a single item in the Geriatric Depression Scale (GDS). Variables were analysed using the binary logistic regression model for identification of risk factors. A total of 293 older people with mean age of 69.1 years old was recruited. The SCD proportion in this study was 24.6%. One unit increase in Geriatric Depression Scale (GDS) score increases risk of subjective cognitive decline by odds of 1.814 (OR=0.595: 95% CI:1.441–2.283; p<0.001). Meanwhile, those with diabetes have a tendency of 2.972 to have SCD as compared to non-diabetics (OR=1.089: 95% CI:1.062–8.315; p<0.038). The prevalence of SCD in this study is high and may contribute to cognitive impairment. The predictors of SCD were larger waist circumference, having diabetes, and increasing score in GDS. SCD must be screened earlier and healthy lifestyle must be emphasized. Routine screening and monitoring of non-communicable disease risk factors are important for the prevention of SCD.